Use of Ceramic Membrane Technology for Sustainable Management of Oil Production Water: A Review - Al-Haddabi, M.; Vuthaluru, Hari; Ahmed, M.; Znad, Hussein (Springer International Publishing, 2015)
The huge quantities of water produced a long with oil makes it one of the main challenges in oil and gas industry. In the past the oily produced water was considered as a tiresome by-product and it represent a significant liability and cost to the oil and gas production. Recently this attitude has changed and the oily produced water is now seen more as a resource than a by-product. By 2025, 2.8 billion people (from 48 countries) will be living in water-scare and water-stressed countries. Sultanate of Oman is considered as a semi-arid country where the average annual rainfall is about 100 mm. Petroleum Development Oman (PDO) which is an oil company produces around 700,000 m3/day of water associated with hydrocarbon production. Currently under half of this amount is rejected back into the producing reservoirs as water flood for reservoir management. The production of excessive quantities of water is the reason behind to abandon oil and gas wells, leaving huge quantities of hydrocarbons behind. Upgrading of low quality water (i.e. oily produced water) for greening the desert or growing biofuels is becoming a strategic enabler for the sustainable development of remote fields. Although opportunities exist for beneficial use of oily produced water, there may be situations where treatment may not be economically feasible.In addition to volume, water quality is the other key determinant of suitable management options. Due to the poor quality of oily produced water (because oily produced water contains a complex mixture of organic and inorganic materials similar to those found in crude oil and natural gas), treatment might introduces potential economic, technology and environmental challenges. Another constraint for the management of oily produced water is the regulatory framework which might cause restrictions to management options imposed by legislations. Economic constraint imposed by the costs associated with management options can influence the feasibility of particular management techniques. The application of ceramic membrane have shown great potential for the oil in water separation and purification due to their superior mechanical, thermal, chemical stability and ease of generation after fouling. Very promising results were achieved by many researchers when using ceramic membranes for oily water treatment. In some studies the removal of oil, COD and TOC reach up to 99%, 96% and 94% respectively.